Diagnostic Dilemma: Large Primary Ovarian Leiomyoma Imitating Fibroma in a Postmenopausal Patient: Case Report. - Ruchi Sinha; Preetika Sinha; Tarun Kumar; Avinash Singh; Shankhanila Mazumdar (SJ Gynecology and Obstetrics Africa, 2026)
Primary ovarian leiomyoma is extremely uncommon, with a low incidence rate of 0.5-1% of benign ovarian tumors. Due to its rarity, it poses a diagnostic dilemma and needs to be differentiated from other spindle cell neoplasms of the ovary. We report a case of a large symptomatic primary ovarian leiomyoma in a postmenopausal woman, which was misdiagnosed as fibroma of the ovary both clinically and radiologically. Microscopy revealed a spindle cell tumor arranged in short intersecting fascicles, which were positive for SMA and h-caldesmon on immunohistochemistry. is a useful adjunct for definitive diagnosis and confirming smooth muscle origin. While malignant solid ovarian tumors are much more common, the consideration of ovarian leiomyoma as a differential diagnosis of solid ovarian tumors is essential, as the treatment modality is surgical resection. Diagnosing ovarian leiomyoma before and during surgery is challenging. It is advisable to perform both histopathological examination and immunohistochemical analysis.